Increasing the Capacity of the Unsignalized Three Way Petir Intersection, Serang Regency - Prasetyo Artiwi, Nila; Rosdiyani, Telly (ASTONJADRO, 2022)
Population growth increases every year, especially in Serang Regency, causing traffic problems including accidents, congestion, or being faced with conditions of frequent road scrambling. In preliminary observations, this happened to the Unsignalized Three Way Petir Intersection . This research was conducted to determine the existing performance of the intersection and find alternative solutions to overcome the problem situation and find out the cost needs needed in planning the proposal. Thus, of course, data is needed to be able to analyze it. The method used is based on the Indonesian Road Capacity Manual (MKJI) of 1997, the required data consists of primary data by conducting a field survey, to find out the volume of vehicles (Average daily traffic / ADT for seven days from 06.00 to 18.00 WIB, road geometrics, traffic conditions, and environmental conditions. It is known that the Unsignalized Three Way Petir Intersection type is type 322, meaning 3 arms 2 lanes 2 directions, the data uses the form USIG I and the form USIG II from MKJI 1997. The results showed that the existing performance at the Unsignalized Three Way Petir Intersection showed the largest total traffic flow value of 3,480 passenger car unit (pcu) / hour, the saturation degree (DS) value was 1,026, which means, the traffic flow has exceeded the road capacity, with an intersection traffic delay of 16,426 sec / pcu, a delay in main road traffic (B-D) of 7.4584 sec / pcu and a delay in minor road traffic (C) of 38.2352 sec / pcu, queue odds are between 42.3554% to 84%. Alternative solutions that can be done prohibit the right turn traffic from minor roads, as well as widening on the main road from 3 m per lane to 3.5 m so that the short width of each lane = 3.5 m and the shoulder width of 0.5 m, in total to 8 m, so that the cost required in the planning is Rp. 2,220,051,000 (two billion two hundred twenty million fifty-one thousand rupiah).